(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Doctors have repeatedly observed the peculiarities of the course of diseases of the gastroduodenal zone in alcoholic diseases, their resistance to traditional methods of treatment, the tendency to frequent development of gastrointestinal bleeding and other complications leading to the death of the patient [3].